Faktor Penyebab Terjadinya Ikhtilaf di Kalangan Imam Mujtahid dan Implikasinya terhadap Hukum Islam Kontemporer - Nurhayati Masani; Puti Humairah Djufri; Icksan Asry Fabanjo; Mustamin Giling (Al-Kindi, 2026)
Disagreements (Ikhtilaf) among mujtahid imams are an inevitable epistemological phenomenon in the Islamic legal tradition. This article analyzes the factors causing these differences, ranging from differences in understanding of texts, the istinbath method, the acceptance of hadith, to the socio-cultural context surrounding the mujtahids. Using a normative-qualitative approach with a literature review method, this article examines classical sources of ushul fiqh and contemporary literature to understand the epistemological roots of these differences. The research findings demonstrate that these differences are not weaknesses, but rather methodological richness that underpins the flexibility of Islamic law. Furthermore, this article outlines the implications of these differences for contemporary Islamic law in responding to modern issues such as bioethics, Islamic economics, family law, human rights, and societal plurality. The legacy of these differences among the mujtahid imams has proven to be an important foundation for the development of Islamic law that is adaptive, contextual, and remains faithful to the principles of sharia